KKNI Curriculum Management at Islamic Education Management Study Program UIN Raden Fatah Palembang - Rita Yulia Anggraini; Julius Julius; Wawan Ahmad Ridwan; Halimatun Syakdiah; St. Humaerah Syarif (Universitas Pahlawan Tuanku Tambusai, 2022)
This study aims to determine the management of the KKNI Curriculum at the Islamic Education Management Study Program at UIN Raden Fatah Palembang. The type of research used is qualitative research, with a descriptive approach. Data were collected through observation and interview techniques. This study shows that the KKNI curriculum management at the Islamic Education Management Study Program at UIN Raden Fatah Palembang has been running well. This is influenced by human resources, leadership support (Deans to Chancellors), and the MPI UIN Raden Fatah Palembang study program which received A accreditation. In addition, all lecturers and students gave an excellent response to the implementation of the KKNI in the MPI UIN Raden Fatah Palembang study program to improve the quality of students.